Control and spatial distribution of leakage points in urban areas water distribution networks: the case of 3 water distribution sector of the metropolitan area of Belém - Santos, Aline Christian Pimentel Almeida; Pereira, José Almir Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The article demonstrates the importance of control and spatial occurrence of leakage points in water distribution networks in urban areas, using the case of 3 of the metropolitan region of Belém water distribution sector. The study was conducted in four stages. In step 1 data was collected from the study area. Step 2 was for the construction of georeferenced database and organization of cartographic information. In steps 3 and 4 were carried out the classification and the crossing of the data obtained using Geographic Information System, respectively. Among the information spatialized are the number of leaks by date of occurrence, for material, pipe diameter, by street, neighborhood by, among others. During the period analyzed were detected 248 leaks, and you can view the street and the neighborhood with the highest incidence, location and the material more conducive pipe leaks, the length of time etc. With the work we found that the data logging and crossing of information in GIS is an alternative to the update, monitoring of operating activities, and effective solution for controlling leaks in distribution networks of drinking water.